Additionality, Mistakes, and Energy Efficiency Investment - Gilbert, Ben; LaRiviere, Jacob; Novan, Kevin (2019)
Investment subsidies, like those for energy efficiency upgrades, often suffer from poor additionality. Using a novel theoretical model, we show when benefits from investments are uncertain, subsidy policies can also lead to inefficient investment decisions that don't pass the full information benefit cost test. We use a unique household-level dataset of energy efficiency audits and investments to test model predictions. We find that households are significantly more likely to schedule audits and installs when first moving into an existing home when, ironically, information uncertainty is greatest. We then build on the theoretical model to inform better policy design.
No 2019-01, Working Papers from Colorado School of Mines, Division of Economics and Business